Strategic environmental assessments for genetically modified organisms - Linacre, Nicholas A.; Gaskell, Joanne; Rosegrant, Mark W.; Falck-Zepeda, José B.; Quemada, Hector; Halsey, Mark; Birner, Regina (Informa UK Limited, 2006)
Genetically modified crops appear to provide a promising option in finding sustainable solutions to end global hunger and poverty, but strategic decisions need to be made on how to spend limited agricultural research funds. Potentially, strategic environmental assessment (SEA) may be used as part of an environmental management system to introduce mainstreaming of environmental considerations in the policy research and priority-setting process of development organizations to help achieve international development goals. This paper sets out a possible biotechnology SEA process that integrates qualitative and quantitative assessments with a focus on risk assessment and management within the SEA and policy environmental assessment frameworks. It uses the International Association for Impact Assessment six performance criteria for SEAs: integration; sustainability; focus; accountability; participation; and iteration.